POLITIK DAKWAH DAN DAKWAH POLITIK DI ERA REFORMASI INDONESIA - Andi Rosa (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This research activity parse dzikir majelis Susilo Bambang Yudhoyono (SBY) "Nurussalam" which has a strategic role in the democratic era. His status as a society organizations (NGOs) are positioned optimally by interest groups, political organizations and even into the container. By analyzing the dataobtained through interviews and documentation, the results of this study indicate that this council makes verses of the Qur’an that deals with the concept of al-‘ummah, al-ukhuwwah al-islamiyya, and al-ta'āwun as a cornerstone in interpreting paragraph integrative social which is then used as a propaganda entity. Proselytizing as mass communication, political communication line with more likely to use communication as a way to mobilize the masses massif. Even activities have been able to carry out the functions of political propaganda as part of the interest-group system.